Adsorption in one-dimensional channels arranged in a triangular structure: Theory and Monte Carlo simulations - Davila, Mara Veronica (2007)
Adsorption thermodynamics of interacting particles adsorbed on one-dimensional channels arranged in a triangular cross-sectional structure is studied through Bragg-Williams approximation (BWA), Monte Carlo (MC) simulations and the recently reported Effective Substates approximation (ESA) [J.L. Riccardo, G. Zgrablich, W. A. Steele, Appl. Surf. Sci. 196 (2002) 138]. Two kinds of lateral interaction energies have been considered: (1) wL, interaction energy between nearest-neighbor particles adsorbed along a single channel and (2) wT, interaction energy between particles adsorbed across nearest-neighbor channels. We focus on the case of repulsive transversal interactions (wT > 0), for which a rich variety of ordered phases are observed in the adlayer, depending on the value of the parameters kB T / wT (being kB the Boltzmann constant) and wL / wT. Comparisons between analytical data and MC simulations are performed in order to test the validity of the theoretical models. Appreciable differences can be seen for the different approximations, ESA being the most accurate for all cases.